Impact of serogroup A meningococcal conjugate vaccine for Africa - James M. Stuart (Taylor & Francis Group, 2018)
The introduction of a serogroup A meningococcal conjugate vaccine in the African meningitis belt has been a remarkable success. Meningitis due to the serogroup A meningococcus, previously responsible for most epidemics, has fallen by 99% in vaccinated countries. Success must, however, not distract from the continuing burden of meningitis in this region of Africa. The number of all meningitis epidemics at health district level has fallen by 60% following vaccination, but epidemics due to other meningococcal serogroups continue and may be increasing. The introduction of low cost multivalent conjugate vaccines must be given high public health priority.